2016
DOI: 10.18203/issn.2454-5929.ijohns20162877
|View full text |Cite
|
Sign up to set email alerts
|

Role of high resolution computed tomography of temporal bone in management of chronic suppurative otitis media

Abstract: INTRODUCTIONConventional radiography of the temporal bone (X-Ray mastoid bone) has not kept pace with the progress of modern otology and for this reason many otologists have felt that radiography of the temporal bone is of little value in CSOM. The diagnosis may be made entirely on clinical grounds and many surgeons feel that with experience and careful techniques the extent and nature of the pathology can be determined during the course of surgical exploration without prior information being required.The adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
6
5
0
Order By: Relevance
“…Similar results were also noted in study by Niveditha et al and Rai et al 2,17 The dural plate is best observed in the coronal plane and as a thin bone plaque covering the epitympanum and the mastoid (Figure 3). 11 In our study, HRCT temporal bone was found to be 100% sensitive and specific in identifying tegmen tympani erosion which is in consonance with studies by Tak et al and Chatterjee et al 9,16 Sinus plate erosion was seen in 20% of cases with 85.7% sensitivity and 100% specificity (Figure 4). Chatterjee et al have reported almost similar findings in their study of 167 patients showing 88.89% sensitivity and a specificity of 100%.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar results were also noted in study by Niveditha et al and Rai et al 2,17 The dural plate is best observed in the coronal plane and as a thin bone plaque covering the epitympanum and the mastoid (Figure 3). 11 In our study, HRCT temporal bone was found to be 100% sensitive and specific in identifying tegmen tympani erosion which is in consonance with studies by Tak et al and Chatterjee et al 9,16 Sinus plate erosion was seen in 20% of cases with 85.7% sensitivity and 100% specificity (Figure 4). Chatterjee et al have reported almost similar findings in their study of 167 patients showing 88.89% sensitivity and a specificity of 100%.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, HRCT was found to have less sensitivity in differentiating cholesteatoma from granulations which is in consonance with other studies. [8][9][10][11] HRCT was found to be helpful in correctly picking out extent of the disease which is in agreement with studies by Donoghue et al and Mafee et al 12,13 Early radiological sign of cholesteatoma is bone erosion. In our study, all cases (90%) reported in CT were confirmed at surgery.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Incus was the most common ossicle eroded (68%) with sensitivity of 91.8% and specificity of 100%. This is in accordance with the findings by Tak and Khilnani who found 91% sensitivity and 100% specificity [19]. Malleus was the next most commonly eroded ossicle after incus, seen in 48% of cases with sensitivity of 88.8% and specificity of 92.8% which is correlating to the study by Prakash and Tarannum who found 89.4% sensitivity and 90.9% specificity [5].…”
Section: Discussionsupporting
confidence: 91%
“…2 the facial nerve, tegmen and sinus plate and determining dural sigmoid sinus and jugular bulb status. 3 Accurate identification of the nature, site, size, extension and invasion into adjacent structures and tissue plane including the intracranial extension has been made possible by HRCT thereby affecting the course of the management. 4 The use of HRCT in the preoperative evaluation of the patient with chronic otitis media is still controversial.…”
Section: Introductionmentioning
confidence: 99%